Character Education For The Modern Generation: Revitalizing The Traditional Istighotsah Program In An Indonesian Madrasah - Wibowo, Krisna Aditiya; Sutiah, Sutiah (Proceeding of International Conference on Islamic Education (ICIED); Vol 10 No 1 (2025): Proceeding of International Conference on Islamic Education (ICIED), 2025)
Forming religious character is an urgent component of Islamic education in the modern era; this study examines how a traditional spiritual practice is revitalized as a tool for character education in an Indonesian madrasah. This research aims to describe the implementation of the traditional Istighotsah (collective prayer) program and analyze its contribution to fostering students' religious character, specifically focusing on discipline, responsibility, and politeness. This study employed a qualitative descriptive method, gathering data through observation, in-depth interviews, and documentation with school leadership, teachers, and students. The findings reveal that the routine Friday Istighotsah program, implemented through spiritual habituation, functions as an effective medium for character education. Students demonstrated measurable improvements in punctuality (discipline), active participation (responsibility), and respectful behavior (politeness), reflecting a successful internalization of Islamic values. This study concludes that revitalizing the traditional Istighotsah program offers a significant and replicable model for impactful character education, demonstrating that spiritual practices can be effectively integrated into modern schooling to foster tangible religious character.